Novel Agents and New Combination Treatments on Phase I Studies on Solid Tumors and Pancreatic Cancer - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad W (JOP. Journal of the Pancreas, 2012)
Pancreatic cancer is a relatively rare malignancy with a very aggressive natural course, not restrained by the existing current treatments. At the 2012 American Society of Clinical Oncology (ASCO) Annual Meeting, the results of few phase I clinical studies on solid tumors and pancreatic cancer were presented. In particular, in the field of immunotherapy, a pilot phase I study tested for first time a carcinoembryonic antigen (CEA)-based vaccine (Abstract #2561) on patients with pancreatic adenocarcinoma and another one the optimal dose and efficacy of trabedersen, an inhibitor of tissue growth factor-beta 2 (TGF-β2) aiming to enhance antitumor immune responses (Abstract #4034). Other phase I studies explored the pharmacokinetic and pharmacodynamic properties of an oral gemcitabine pro-drug (LY2334737; Abstract #2554), or of the combination of gemcitabine with sirolimus (Abstract #3096) or the combination of gemcitabine with an inhibitor of mitogen-activated protein kinase (MAPK), extracellular signal-regulated protein kinase (ERK) (MEK 1/2; Abstract #4034). Image: Athena (Logo of the National and Kapodistrian University of Athens. Athens, Greece).